2006
DOI: 10.1094/pd-90-0832b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Begomovirus Infecting Sweetpotato in Kenya

Abstract: Previous surveys for viruses in sweetpotatoes (Ipomoea batatas) in Africa did not assay for the presence of begomoviruses such as Sweet potato leaf curl virus (SPLCV), which have been found recently in the Americas and Asia. Symptomatic sweetpotato plants, including some with leaf curling symptoms similar to those observed in SPLCV-infected sweet-potato plants (2), were collected from a germplasm collection plot at Kakamega Research Station in Western Kenya during February 2005. Whiteflies, the vectors for beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
2
23
1
1
Order By: Relevance
“…Among the regions, Western Kenya had the highest risk of SPLCV followed by Coast region and Central region with the lowest. The results obtained in this study reported the presence of SPLCV in Western Kenya, in agreement with previous studies that SPLCV was present in the region and they are (Miano et al, 2006). The presence and high incidence of the virus in the Coast region was not expected.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the regions, Western Kenya had the highest risk of SPLCV followed by Coast region and Central region with the lowest. The results obtained in this study reported the presence of SPLCV in Western Kenya, in agreement with previous studies that SPLCV was present in the region and they are (Miano et al, 2006). The presence and high incidence of the virus in the Coast region was not expected.…”
Section: Discussionsupporting
confidence: 92%
“…Several of these viruses occur in East Africa, including SPFMV, (genus Potyvirus), Sweet potato mild mottle virus (SPMMV, genus Ipomovirus). Others includes those in the family Closteroviridae which, includes SPCSV (genus Crinivirus), Sweet potato chlorotic fleck virus (SPCFV, genus Carlavirus) and Sweet potato leaf curl virus (SPLCV, genus begomovirus) (Ateka et al, 2004;Miano et al, 2006;Wasswa et al, 2011). SPLCV is transmitted by Bemisia tabaci or through vegetative propagation.…”
Section: Sweet Potato (Ipomoea Batatasmentioning
confidence: 99%
See 1 more Smart Citation
“…These are: sweet potato leaf curl virus (SPLCV) (Lotrakul et al, 1998;Lotrakul & Valverde., 1999), Ipomoea yellow vein virus (IYVV) (Banks et al, 1999) and sweet potato leaf curl Georgia virus (SPLCGV) (Lotrakul et al, 2003). SPLCV or related begomoviruses have been isolated from sweet potato in the Americas (Lotrakul et al, 2003;Fuentes & Salazar, 2003), Asia (Onuki & Hanada, 1998;Luan et al, 2006) and Africa (Miano et al, 2006) and from I. indica in Europe . Begomoviruses are likely to be present in many regions where sweet potato is grown but their prevalence and distribution is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Begomoviruses infect Ipomoea plant species worldwide and have been identified in Japan, Israel, Peru, Italy, Spain, China, Taiwan, Korea, Kenya, and USA (Chung et al, 1985;Osaki and Inouye, 1991;Banks et al, 1999;Lotrakul et al, 2003;Fuentes and Salazar, 2003;Briddon et al, 2006;Miano et al, 2006;Simmons et al, 2009). Several begomovirus species (SPLCV, IYVV, SPLCGV, SPLCCaV, SPLCLaV, SPLCESV, SPGVaV, and SPMaV) have been reported to infect Ipomoea species and their genomes have been fully sequenced (Lotrakul et al, 1998;Banks et al, 1999;Lotrakul et al, 2003;Lozano et al, 2009;Paprotka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%